EVALUASI PEMBANGUNAN INFRASTRUKTUR DESA SEBAGAI UPAYA PENINGKATAN TATA KELOLA PEMERINTAHAN - Adi Putra, Dwiki; Febrianti Dewi, Kartika; Isabella (Governance, 2025)
Evaluation is a process of providing information about the extent to which a particular activity has been achieved. Village infrastructure development is an important effort in improving the welfare of rural communities. Adequate infrastructure, such as roads, bridges, and access to clean water, plays an important role in supporting economic, social, and cultural activities in villages. The purpose of this writing is to find out how the evaluation of village infrastructure development as an effort to improve governance (Case Study in Talang Bulang Village, Talang Ubi District, Penukal Abab Lematang, Ilir Regency). In this research, the author uses a qualitative research method by looking directly at the phenomena that are currently occurring and developing in the environmental situation. Qualitative research methods are a type of approach used to describe, investigate, and understand problems that many individuals or groups of people believe are related to social or personal problems. Then the data collection methods used are observation, interviews, and documentation. This study focuses on the evaluation of village infrastructure development as an effort to improve governance in Talang Bulang Village, Talang Ubi District, Penukal Abab Lematang, Ilir Regency, using four main indicators: context evaluation, input evaluation, procces evaluation, and product evaluation which is the theoretical model of Daniel L. Stuflebeam. Based on the results of the analysis and findings carried out in the evaluation of village infrastructure development as an effort to improve government governance in Talang Bulang Village has been running well starting from planning, development, participation, and community involvement in village infrastructure development. Because it has been explained in Law Number 06 of 2014 concerning villages that must involve the community in terms of development and planning because the people who know the conditions of the region are the people themselves.